Place-Naming (Toponymy) of Kecamatan in Bandung: A Morphological Study - Intan Siti Nugraha; Lia Maulia Indrayani; Ypsi Soeria Soemantri (Institut Agama Islam Negeri Palopo, 2020)
This study aims to analyze the morphological processes occupied in place-naming of Kecamatan in Bandung and attempts to classify the place-naming of Kecamatan in Bandung based on toponymy rules by Nash (2015). Descriptive qualitative research design was employed in this study. The investigation of thirty names of Kecamatan in Bandung shows that there are only three types of morphological process in naming Kecamatan in Bandung. They are compounding, borrowing and blending. In term of toponymy rules, the patterns are various in each morphological process: (1) A Single (Proper) Noun; (2) Two Nouns: (Generic) Noun + (Proper) Noun; and (3) (Proper) Noun + Adjective.